Beam radiation penetration in particle beds for heat transfer modeling of a centrifugal solar particle receiver. (January 2023) - Johnson, Evan; Hicdurmaz, Serdar; Buck, Reiner; Hoffschmidt, Bernhard
Highlights: Monte Carlo Ray Tracing performed for beam (direct) radiation striking particle beds. Total bed absorptivity found as a function of angle, absorptivity, solid fraction. Heat transfer model for Discrete Element Method developed for incident radiation. Model applied to CentRec solar receiver, where particles are unsettled and dynamic. MCRT code is published open source, capable of diffuse and specular reflections. Abstract: This article describes a study of beam radiation striking particle beds of randomly packed, spherical particles. The current study is focused on concentrating solar power receivers which use solid particles as a heat transfer medium, but results are applicable to particle beds in various industries. The analyses are carried out using a purpose-built open-source Monte Carlo Ray Tracing code for beam radiation striking a group of particles. Particle beds with a uniform solid fraction and diffuse reflections are studied first, with the total bed absorptivity found for various combinations of the incidence angle, absorptivity, and solid fraction, culminating in an expression for the total bed absorptivity as a function of these independent variables. In addition, the transmitted fraction of incident rays as a function of distance into the bed is given in table format for many sets of these parameters. These results form the foundation of an algorithm developed to estimate the radiation absorption at different depths in the more challenging case where the solid fraction varies as a function of depth in the bed. This is particularly important for the "CentRec" solar receiver, where the solid fraction oscillates due to the thin particle film used in this device (only 4–10 particle diameters thick), as well as the dynamic nature of the particle film. The algorithm is implemented in a Discrete Element Method model for heat transfer in the CentRec receiver, and the algorithm is shown to have a high accuracy with a very low computational cost compared to a full Monte Carlo Ray Tracing simulation.